Meaning of work, satisfaction with life, happiness, and work engagement, among nurses at selected state hospital, Windhoek, Namibia - Ilmalwa, Werner; Hlatywayo, Clifford Kendrick (Health & Research Journal, 2022)
Background: Irrespective of the risk of stress and occupational hazards, health care practitioners, amongst them nurses, stay working in the health care system for years and some remain engaged with their work. Although there are many determinants of work engagement within organizations, the present study explored the association between meaning of work, satisfaction with life, happiness and work engagement. Material and Method: The self-determination theory was adopted to extrapolate the relationship amongst variables. A self-administered questionnaire was used to measure meaning of work, satisfaction with life, happiness and work engagement. The study sample comprised of 142 nurses employed at public sector hospitals in Windhoek, Namibia. Pearson correlation coefficient and regression were used to analyze data. Results: The results showed a negative relationship between meaning of work and subjective happiness; meaning of work had no significantly relationship to satisfaction with life; Satisfaction with life was statistically related to subjective happiness; and a negative significant relationship between meaning of work and work engagement. Happiness and meaning of work had a significant relationship; work engagement was related to subjective happiness. Employee engagement accounted for a 15% variation to the relationship. Conclusion: Regular interactions with the nurses is necessary to have the opportunity to consider individual needs some nurses need extra training in certain procedures, job resources such as social support from colleagues and supervisors, performance feedback, skill variety, autonomy, and learning opportunities are advocated for.